2020
DOI: 10.1155/2020/9206703
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Matrix Metalloproteinase-28 Levels Are Related to GRACE Scores and Short-Term Outcomes in Patients with Acute Myocardial Infarction

Abstract: Objective. To investigate the relationship between the level of matrix metalloproteinase-28 (MMP-28) in patients with acute myocardial infarction (AMI) and the global registry of acute coronary events (GRACE) scores as well as their short-term prognosis. Methods. Two hundred eleven patients with AMI were enrolled, and their basic clinical characteristics were collected for determining the GRACE score. We measured the plasma levels of MMP-28 and other biomarkers in the study population. The association of MMP-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Expression of ERRFI1 190 , ALOX12 191 , SOCS5 192 , DDIT4 193 , DUSP4 194 , IL6ST 195 , DUSP1 196 , SMAD1 197 , NCL (nucleolin) 198 , METTL14 199 , FMOD (fibromodulin) 200 , CYGB (cytoglobin) 201 , UNC5A 202 and TAAR9 203 are believed to be associated with diabetic nephropathy. Genes include FAP (fibroblast activation protein alpha) 204 , EYA4 205 , BCL9 206 , IRF2BP2 207 , EGR3 208 , GADD45B 209 , DMD (dystrophin) 210 , LSR (lipolysis stimulated lipoprotein receptor) 211 , DLL4 212 , SUN2 213 , SOS1 214 , PIK3CA 215 , GAMT (guanidinoacetate N -methyltransferase) 216 , RBM47 217 , HSP90AA1 218 , GAB1 219 , S1PR1 220 , EDNRB (endothelin receptor type B) 221 , NFKBIA (NFKB inhibitor alpha) 222 , GJA1 223 , GADD45G 224 , PHLDA1 225 , CMPK2 226 , FIGN (fidgetin, microtubule severing factor) 227 , KCNJ2 228 , ABCC9 229 , DIRAS3 230 , EPHX1 231 , RAB4A 232 , UBIAD1 233 , CASQ2 234 , TTN (titin) 235 , KCNH1 236 , JPH2 237 , OXGR1 238 , UCHL1 239 , SERPINA3 240 , MMP28 241 , ADAMTS2 242 , P2RY1 243 , CSF2RA 244 , MYO1F …”
Section: Discussionmentioning
confidence: 99%
“…Expression of ERRFI1 190 , ALOX12 191 , SOCS5 192 , DDIT4 193 , DUSP4 194 , IL6ST 195 , DUSP1 196 , SMAD1 197 , NCL (nucleolin) 198 , METTL14 199 , FMOD (fibromodulin) 200 , CYGB (cytoglobin) 201 , UNC5A 202 and TAAR9 203 are believed to be associated with diabetic nephropathy. Genes include FAP (fibroblast activation protein alpha) 204 , EYA4 205 , BCL9 206 , IRF2BP2 207 , EGR3 208 , GADD45B 209 , DMD (dystrophin) 210 , LSR (lipolysis stimulated lipoprotein receptor) 211 , DLL4 212 , SUN2 213 , SOS1 214 , PIK3CA 215 , GAMT (guanidinoacetate N -methyltransferase) 216 , RBM47 217 , HSP90AA1 218 , GAB1 219 , S1PR1 220 , EDNRB (endothelin receptor type B) 221 , NFKBIA (NFKB inhibitor alpha) 222 , GJA1 223 , GADD45G 224 , PHLDA1 225 , CMPK2 226 , FIGN (fidgetin, microtubule severing factor) 227 , KCNJ2 228 , ABCC9 229 , DIRAS3 230 , EPHX1 231 , RAB4A 232 , UBIAD1 233 , CASQ2 234 , TTN (titin) 235 , KCNH1 236 , JPH2 237 , OXGR1 238 , UCHL1 239 , SERPINA3 240 , MMP28 241 , ADAMTS2 242 , P2RY1 243 , CSF2RA 244 , MYO1F …”
Section: Discussionmentioning
confidence: 99%
“…MMPs play a pivotal role in post-myocardial infarction cardiac remodeling as well as in the development of adverse outcomes ( 115 ). Circulating MMP-28, a new member in the family of MMPs, could be considered a predictor for short-term prognosis in patients with myocardial infarction ( 73 ).…”
Section: Biomarkersmentioning
confidence: 99%
“…The potential role in the development of atherosclerosis and acute coronary syndromes of a group of zinc-dependent endopeptidases, namely, matrix metalloproteinases (MMPs), was investigated in previous studies [ 70 , 71 , 72 ].…”
Section: Newer Biomarkers For Laboratory Diagnosis Of Acute Myocardial Infarctionmentioning
confidence: 99%
“…Due to matrix metalloproteinase-9 linking with plaque rupture and myocardial necrosis, MMP-9 has demonstrated its position as an early-stage biomarker of AMI [ 70 ]. It was also suggested that the value of MMP-28 correlates with GRACE score and could be a predictor of short-term prognoses in AMI cases [ 72 ].…”
Section: Newer Biomarkers For Laboratory Diagnosis Of Acute Myocardial Infarctionmentioning
confidence: 99%